In-Silico Analysis of Momordica charantia L. As Antidiabetic Agents Through Activation of Human UDP-Galactose 4-Epimerase Receptors - Pramesthi, Asri Dwi Endah Dewi; Suwarno, Kafka Navisa; Pratama, Aldo; Rasyidah, Jamiatur; I Wayan Surya Rahadi; Rasida, Rima (Jurusan Farmasi Poltekkes kemenkes Makassar, 2024)
This study investigates the antidiabetic potential of compounds found in Momordica charantia L., commonly known as bitter melon, through molecular docking and ADME (Absorption, Distribution, Metabolism, and Excretion) analysis. Utilizing in silico methods, several bioactive compounds from bitter melon, such as charantin, vicine, momordenol, momordicilin, and momordicoside, were evaluated for their ability to interact with the human UDP-Galactose 4-Epimerase receptor, a key enzyme involved in glucose metabolism. The docking results indicate that these compounds exhibit strong binding affinities, suggesting their role in glucose regulation. Further ADME analysis revealed that the compounds generally comply with the Lipinski Rule of Five, indicating favorable drug-like properties, though some compounds exhibited potential toxicities requiring further investigation. These findings highlight the potential of Momordica charantia as a source of antidiabetic agents, warranting additional in vivo and clinical studies to confirm their efficacy and safety in managing diabetes mellitus.